Update in the Treatment of Retinopathy of Prematurity - Bancalari, Aldo; Schade, Ricardo (American Journal of Perinatology, 2020)
Retinopathy of prematurity (ROP) is an alteration in the development of the immature retina vascularization that frequently occurs in premature infants and is one of the leading causes of childhood blindness worldwide. In threshold stage retinopathy, laser photocoagulation is the standard treatment, particularly in those located in zone II. However, this therapy destroys parts of the retina and can lead to significant eye complications later in life. For this reason, in the last few years, antivascular endothelial growth factor agents are being used as monotherapy or as coadjuvant with laser, especially in retinopathy located in zone I. More recently, the administration of oral propranolol has been used as prevention and/or treatment of prethreshold retinopathy with encouraging results. This review provides an overview of the current evidence on newer treatment strategies for ROP.Key Points
Keywords: retinopathy of prematurity; laser; anti-VEGF agents; bevacizumab; propranolol